Organic Fertilizer from Amino Acid and Eco-Enzyme Combinations for Repairing Plant Metabolism - Satrio, Galih; Hanum Hasibuan, Anggi Khairina; Azzida, Putry Wanda (Indonesian Scholar Society, 2023)
At Gadog Fresh, eco-enzymes and amino acids are the revolutionary combination of liquid organic fertilizers used to attain a zero-waste lifestyle. This research determined the effect of various liquid organic fertilizers on improving the metabolism of leek plants. This research was conducted at the Gadog Farm. The method applied liquid organic fertilizers from eco-enzymes and chicken eggs in the treatment labeled K, P1, P2, and P3 with various doses of 0.0; 2.5; 5.0; and 7.5 mL/L into spring onions. It was applied as much as 250 mL four times every seven days. The results obtained were plant height, namely 36.45; 47.63; 41.52; 42.62; stem diameter 7.30; 8.92; 10.42; 9.42; and dry weight percent 7.07; 7.38; 9.05; 7.09. The increase in height, diameter, and dry weight showed that liquid organic fertilizer applications improved the metabolism of leek plants. However, variations in the concentration of liquid organic fertilizer did not significantly affect all research points.